A review of the wire arc additive manufacturing of metals: properties, defects and quality improvement. (October 2018) - Wu, Bintao; Pan, Zengxi; Ding, Donghong; Cuiuri, Dominic; Li, Huijun; Xu, Jing; Norrish, John
Graphical abstract: Abstract: Due to the feasibility of economically producing large-scale metal components with relatively high deposition rates, significant progress has been made in the understanding of the Wire Arc Additive Manufacturing (WAAM) process, as well as the microstructure and mechanical properties of the fabricated components. As WAAM has evolved, a wide range of materials have become associated with the process and its applications. This article reviews the emerging research on WAAM techniques and the commonly used metallic feedstock materials, and also provides a comprehensive over view of the metallurgical and material properties of the deposited parts. Common defects produced in WAAM components using different alloys are described, including deformation, porosity, and cracking. Methods for improving the fabrication quality of the additively manufactured components are discussed, taking into account the requirements of the various alloys. This paper concludes that the wide application of WAAM still presents many challenges, and these may need to be addressed in specific ways for different materials in order to achieve an operational system in an acceptable time frame. The integration of materials and manufacturing process to produce defect-free and structurally-sound deposited parts remains a crucial effort into the future.